Digital Marketing Strategy at SOD Group in Increasing Interest in Purchasing Concert Tickets Sounds of Downtown Festival in Surabaya - Arifania Pratiwi; Indah Respati Kusumasari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The existence of business development supported by technology has become the backbone for many companies that want to survive and thrive in the midst of increasingly rapid business changes by implementing digital marketing in their business. Companies can implement digital marketing as part of their strategy to keep up with fast-moving market trends. This research highlights SOD Group's digital marketing strategy in increasing interest in purchasing Sounds Of Downtown Festival concert tickets. The purpose of this research is to analyze the effectiveness of digital marketing strategies implemented by SOD Group in influencing concert ticket purchasing decisions. The type of research used is qualitative research with a descriptive approach. The data analysis method used is SWOT analysis to identify strengths, weaknesses, opportunities, and threats. The results of the research analysis using the IFAS and EFAS tables show that Sounds Of Downtown Festival has four main factors. Strength factors with a total score of 3.09, weakness factors get a total score of 0.38, opportunity factors get a total score of 2.12, and threat factors have a total score of 0.80. Based on the consequences of the SWOT line, Sounds Of Downtown Festival is in quadrant I with a value of (X;Y) (2.71 - 1.32) which indicates a strategic position to implement aggressive strategic planning.